A hierarchical carbon fiber/sulfur composite as cathode material for Li–S batteries. (May 2015) - Wu, Feng; Shi, Lili; Mu, Daobin; Xu, Hongliang; Wu, Borong
Abstract: A novel hierarchical structure carbon/sulfur composite is presented based on carbon fiber matrices, which are synthesized by electrospinning. The fibers are constituted with hollow graphitized carbon spheres formed using catalytic Ni nano-particles as hard templates. Sulfur is loaded to the carbon substrates via thermal vaporization. The structure and composition of the hierarchical carbon fiber/S composite are characterized with X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, and nitrogen adsorption isotherms. The electrochemical performance is evaluated by cyclic voltammetry and galvanostatic charge–discharge. The results exhibit an initial discharge capacity of 845 mA h g −1 at 0.25 C (420 mA g −1 ), with a retention of 77% after 100 cycles. A discharge capacity of 533 mA h g −1 is still attainable when the rate is up to 1.0 C. The good cycling performance and rate capability are contributed to the uniform dispersion of sulfur, the conductive network of carbon fibers and hollow graphitized carbon spheres.